Interaction between the localized states in graphene - Ghosh, Angsula [UNESP]; Frota, H. O. (Elsevier B.V., 2018)
The formation of the localized magnetic moments is studied due to the presence of two-impurities in the two sublattices of a single-layer graphene sheet. The interaction between two similar magnetic impurities and also the hybridizations are decisive in determining the boundary between the magnetic and the non-magnetic states. A strong chemical potential dependence of the above phase boundary is evident. An anomalous scaling of the boundary separating the above regions is more pronounced in the two-impurity case when compared to that of the single impurity. (C) 2018 Elsevier B.V. All rights reserved.
Keywords: Graphene; Adatoms; Phase transition